Ice Cold - Gerritsen, Tess; Sirois, Tanya Eby (Grand Haven, MI Brilliance Audio, 2010)
Stranded with her traveling companions in an eerily deserted Wyoming village during a blizzard, Maura discovers that they are being watched and pursues help when a party member is injured, an effort that turns nightmarish when she is abducted into the woods.
Unabridged
Compact discs.
Read by Tanya Eby.
Keywords: Rizzoli, Jane, Detective (Fictitious character) -- Fiction; Isles, Maura (Fictitious character) -- Fiction; Policewomen -- Fiction; Medical examiners (Law) -- Fiction; Abandoned houses -- Fiction; Women forensic pathologists -- Fiction -- Crimes against; Winter storms -- Fiction; Audiobooks; Wyoming -- Fiction; Mystery fiction